2015
DOI: 10.1021/bi501258u
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Superoxide Dismutase: Structural and Functional Roles of His1 and Its H-Bonding Network

Abstract: Crystal structures of nickel-dependent superoxide dismutases (NiSODs) reveal the presence of a H-bonding network formed between the N-H of the apical imidazole ligand from His1 and the Glu17 carboxylate from a neighboring subunit in the hexameric enzyme. This interaction is supported by another intra-subunit H-bond between Glu17 and Arg47. In this study, four mutant NiSOD proteins were produced to experimentally evaluate the roles of this H-bonding network, and compare the results with prior predictions from D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 32 publications
4
30
1
Order By: Relevance
“…Superoxonickel species are proposed to be key reactioni ntermediates in the catalytic cycle of nickel superoxide dismutase. [27,28] This is also ap lausible formulation for the nickel-dioxygen speciesw hich was recently crystallographically characterizedi nn ickel-dependent quercetin 2,4-dioxygenase ( Figure 1). [7] In 2004 Riordana nd co-workersr eported the formation of as ide-on superoxonickel(II) species by reactiono ft he nickel(I) complex [Ni I (PhTt Ad )(CO)] with O 2 .…”
Section: Superoxonickel Speciesmentioning
confidence: 97%
“…Superoxonickel species are proposed to be key reactioni ntermediates in the catalytic cycle of nickel superoxide dismutase. [27,28] This is also ap lausible formulation for the nickel-dioxygen speciesw hich was recently crystallographically characterizedi nn ickel-dependent quercetin 2,4-dioxygenase ( Figure 1). [7] In 2004 Riordana nd co-workersr eported the formation of as ide-on superoxonickel(II) species by reactiono ft he nickel(I) complex [Ni I (PhTt Ad )(CO)] with O 2 .…”
Section: Superoxonickel Speciesmentioning
confidence: 97%
“…The role of this hydrogen-bonding network was studied by altering this network using H1A, R47A, E17A/R47A, E17R/R47E mutants. 72 Metal analysis using ICP-OES showed that these mutants are still capable of binding nickel; and EXAFS analysis showed that the Ni binds in the same site in these mutants as in WT-NiSOD. The mutants displayed decreased thermal stability, which is more pronounced for the ones with altered His1/Glu17 hydrogen bonding.…”
Section: The Role Of the Second Sphere Ligandsmentioning
confidence: 97%
“…The mutants displayed decreased thermal stability, which is more pronounced for the ones with altered His1/Glu17 hydrogen bonding. 72 The mutants that are EPR active (R47A and E17R/R47E) displayed similar hyperfine splitting at the g z peak indicating that the mutants retain the His-on structure. However, the EPR intensities in these two mutants are significantly decreased compared to WT-NiSOD with the intensities being ~15% for R47A and ~8% for E17R/R47E.…”
Section: The Role Of the Second Sphere Ligandsmentioning
confidence: 98%
See 2 more Smart Citations